The penderwicks on gardam street eaudiobook - Birdsall, Jeanne (The Penderwicks, 2008)
With over one million copies sold, this series of modern classics about the charming Penderwick family from National Book Award winner and  New York Times  bestseller Jeanne Birdsall is perfect for fans of Noel Streatfeild and Edward Eager. The Penderwick sisters are home on Gardam Street and ready for an adventure! But the adventure they get isn’t quite what they had in mind. Mr. Penderwick’s sister has decided it’s time for him to start dating—and the girls know that can only mean one thing: disaster. Enter the Save-Daddy Plan—a plot so brilliant, so bold, so funny, that only the Penderwick girls could have come up with it. It’s high jinks, big laughs, and loads of family warmth as the Penderwicks triumphantly return.